Toxocariasis: An Overlooked Neglected Tropical Disease in Latin America - Rodriguez-Morales, Alfonso J. (2025)
Toxocariasis, a zoonotic parasitic infection primarily caused by Toxocara canis and T. cati, remains a neglected yet widespread public health issue in Latin America. This comprehensive review explores its biological, clinical, epidemiological, and socio-economic dimensions, emphasizing the disease’s underrecognition in endemic areas. Transmission occurs through accidental ingestion of embryonated eggs from contaminated environments, particularly affecting children in low-income settings. In humans, larvae migrate aberrantly, causing visceral, ocular, and neurological syndromes with substantial morbidity. The burden is compounded by limited diagnostic infrastructure, inconsistent access to antiparasitic therapy, and inadequate veterinary and environmental controls. High seroprevalence and environmental contamination rates are reported across Latin America, yet toxocariasis is absent from the World Health Organization’s list of neglected tropical diseases (NTDs). Associations with asthma, epilepsy, and other chronic conditions further underscore its public health relevance. Diagnostic challenges arise from the absence of eggs in human feces and the need for specialized serologic and imaging tools. Emerging innovations in rapid diagnostics and vaccine development, particularly within a One Health framework, offer hope for improved control. However, systemic barriers—including socio-economic inequities, lack of awareness, and insufficient political prioritization—continue to hinder progress. This review advocates for the formal recognition of toxocariasis as an NTD, which would catalyze funding, research, and coordinated control measures. Addressing toxocariasis in Latin America requires integrated, multisectoral strategies that prioritize the most vulnerable populations, aligning with broader goals of health equity and zoonotic disease prevention.